Criminal Law Formulation Policy to Prevent Corporate Crimes Conducting Mining in Forest Areas without Permission - Salin Salin; Muhammad Erham Amin; Ahmad Syaufi; Ifrani Ifrani (Lambung Mangkurat Law Journal, 2024)
Corporations carrying out mining activities in forest areas are still widespread, the existing laws and regulations currently in force are still not enough to prevent corporate crimes in the criminal sector without a business permit from the central government, which causes the risk of environmental damage and social disadvantage for the community, which means In the absence of harmonious law enforcement in the field, there is a need for a concept to provide legal certainty regarding the burden of criminal liability for violations by corporations carrying out mining activities without a permit through policy formulation to provide certainty. The purpose of this writing is to know, understand, analyze, describe and discover the concept of criminal law formulation policies in preventing corporate crimes that carry out mining activities in forest areas without ministerial permission. The results of this writing, through the Connectivity Legal Theory, will be believed to provide a breath of fresh air in law enforcement within the police in order to ensnare corporations that carry out covert and organized business activities. This will provide certainty in the basic guidelines. It differs in that the interpretation method is still ambiguous from various points of view and is still difficult to apply without basic references in countries that adhere to the continental European legal system. The idea of law enforcement in realizing an Article which still contains ambiguities but is based on other rules can be used as a reference to strengthen the position of the Article with the following provisions: a. Still relevant in law in the same environment; b. Still in the same hierarchy of laws and regulations; c. Connected regulations provide clarity on legal issues in legislative formulation; d. Bag-connected rules provide clarity in criminal liability